Manganese dioxides for oxygen electrocatalysis in energy conversion and storage systems over full pH range - Yin, Mingming (2021)
The oxygen catalytic reactions including the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are the basis of many energy transformation and storage devices, e.g., fuel cells, metal-air batteries, and electrolysis cells. Extensive trials have been invested to develop earth-abundant oxygen catalysts to lower the cost and to boost the energy efficiency of these electrochemical devices. Among these oxygen catalysts, manganese dioxide (MnO2) is attracting ever-increasing interest owing to its high earth-abundance, low cost, and well-balanced activity-stability performances. In this review, the mechanisms of ORR and OER catalysis, methods for activity enhancement, and various applications of MnO2 oxygen catalysts in energy conversion and storage are summarized and discussed. As the ORR and OER catalysts in the whole pH range, the Mn3+ intermediate in MnO2 is identified as the active center. To optimize the catalytic performance of MnO2, the strategies of heteroatom doping, morphology tuning, heterostructure forming, conductor supporting, defect engineering, and valence regulating are implemented. Moreover, the applications of MnO2 in metal-air batteries, fuel cells and water splitting systems are detailed. Lastly, some prospects of MnO2 oxygen catalysts are proposed for the further development.